A New Decision-Making Approach for Riyadh makes up 50 percent of the non-oil economy of Saudi Arabia - Alsaud, Alanoud Bandar; Yas, Harith; Alatawi, Abeer (The journal of contemporary issues in business and government, 2021)
Saudi Arabia's capital, Riyadh, has grown from a small city of half-million people to a city of more than seven million people in the past fifty years. As the capital city of Saudi Arabia, Riyadh contributes significantly to the non-oil economy in the country. As a result, this study focused on reviewing the existing literature to assess the city's role in the nation's non-oil economy in the last fifty years. The included studies had to be cross- sectional studies, reports, government publications, and ecological studies that reported Riyadh's role in Saudi Arabia's non-oil economy for the past five decades. One hundred twenty-three studies were initially screened to identify relevant sources. Further analysis and exclusion identified fifty relevant sources that were systematically reviewed. The quality of methodological designs was assessed in all the sources reviewed. The results indicate that Riyadh has been the focal city in diversifying the nation's economy. The review depicts that the general proportion of service industries comprised the major developments in the city. Most of the studies pointed out that Saudi Arabian government has pushed hard to make the country and hub for a non-oil and diversified economy. The study's results depict that the government requires a business to have offices in Riyadh even if they may be based in other cities. This move was adopted after the country suffered major economic setbacks every time there was an uncertain and certain fall in oil demand. The city has the largest service industry, manufacturing, construction, and finance in Saudi Arabia.